Toward Sustainable Consumption Behavior in Online Education Industry: The Role of Consumer Value and Social Identity - Jiang, Songyu; Jotikasthira, Nuttapong; Pu, Ruihui (Frontiers in Psychology, 2022)
The prosperous development of online education in the digital age harvested countless consumers. Education for sustainable development is an important proposition for both academic community and practitioner, however current little studies have shed light on Sustainable Consumption Behavior in online education industry (SCBOEI). The Consumer Value Theory and Social Identity Theory as theoretical basis linked with the field of Sustainable Consumption Behavior. This study is to further investigate the role of consumer value and social identity in the relation to Sustainable Consumption Behavior. Putting forward suggestions from this study to online education providers towards sustainable development. Method: Data on the impact of personal value on SCBOEI through a survey method with 552 valid students as respondents are collected from higher education institutions in China. A structural equation modeling approach is employed in this study for data analysis. Results: The result shows at the level of excellent model fit as indicated by all indicators: X2 / DF = 1.053 (< 3), RMSEA = 0.010 (< 0.08), CFI = 0.991, GFI = 0.971, TLI = 0.989, AGF = 0.961 (> 0.9). The results showed that, through social identity, functional value (indirect effect = 0086, P < 0.001), emotional value (indirect effect = 0061, P < 0.001), and social value (indirect effect = 0.073, P < 0.001) influence the variance of SCBOEI. The finding reveals that both theories can explain the SCBOEI of higher education students by showing that functional, social, and emotional values as well as social identity are powerful predictors of the Sustainable Consumption Behavior. The proposed model highlights the mediating role of social identity between SCBOEI and the three values. The functional, emotional, and social values influence SCBOEI directly and through social identity. Implications: The study significantly contributes to market promotion, college students, education planning, and teaching. Online education market personnel and college students can better understand the significance of sustainable development aspect of online education. Teaching and learning activities help lead students to SCBOEI by shaping their values and identities while paying more attention to quality education, knowledge sharing, and social equality.